Italy’s attitude towards the South Slavs before the start of the Paris Peace Conference - Paszkiewicz, Jędrzej (Balcanica Posnaniensia. Acta et studia, 2001)
The article analyzes the origins of the Italian-Yugoslav conflict over the northern and eastern Adriatic coast at the end of the First World War. The author aims to explain the circumstances that led to the deterioration of relations between Italy and the South Slavic peoples even before the opening of the Paris Peace Conference. The study is based on an analysis of diplomatic documents, primary sources, and scholarly works concerning Italian foreign policy and the formation of the Kingdom of Serbs, Croats and Slovenes. The author argues that the principal source of the dispute was the unfulfilled Treaty of London of 1915, in which the Entente powers promised Italy extensive territorial acquisitions along the Adriatic coast. The collapse of Austria-Hungary created favorable conditions for Italian expansion while simultaneously enabling the political mobilization of the South Slavs, who asserted their own claims to the disputed territories. Particular attention is devoted to the views of Foreign Minister Sidney Sonnino, who regarded the development of the Yugoslav movement as a threat to Italy’s strategic interests. The author emphasizes that Italian policy ignored the principle of national self-determination and restricted the access of Slavic states to the sea. The conclusions indicate that the struggle over the Adriatic resulted from a clash between Italian great-power ambitions and the nation-building processes taking place among the South Slavs.